Sufi-Ecofeminist Hermeneutics: Integrating Murata’s Gender Cosmology and Warren’s Critique to Prevent Ecological Oppression - Nikmah, Shofiatun; Hikmawati, Risma; Sitorus Pane, Siti Rif'atus Sa'adah; Jannah, Wardatul; Muzaki, Kiki Adnan (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2026)
The modern ecological crisis, characterised by the exploitation of natural resources and social inequality, has placed women as the most vulnerable group, economically, health-wise, and socially. In this context, this study offers a Sufi-ecofeminist hermeneutic approach as an alternative to a more holistic reading of the Qur'an. Its theoretical foundation integrates Sachiko Murata's Sufi gender cosmology, which emphasises cosmic balance between masculinity and femininity, with Karen Warren's ecofeminist critique that rejects essentialism and highlights patriarchy, capitalism, and colonialism as the roots of oppression against nature and women. The research method uses qualitative analysis based on literature studies, with the main sources being verses from the Qur'an, classical ishari interpretations, and contemporary ecofeminist works. The results show that the integration of Murata and Warren produces a non-essentialist interpretive framework that rejects hierarchy, affirms humans as guardians of cosmic balance, and places ecological concern as part of Islamic spirituality. In conclusion, the Sufi-ecofeminist approach opens up a more inclusive and transformative space for Qur'anic interpretation. As a result, this research not only enriches the discourse on Islamic interpretation and philosophy but also contributes practically to education, da'wah, and ecological policies that are gender-equitable and sustainability-oriented.  Krisis ekologis modern yang ditandai oleh eksploitasi sumber daya alam dan ketimpangan sosial telah menempatkan perempuan sebagai kelompok yang paling rentan, baik dari segi ekonomi, kesehatan, maupun sosial. Dalam konteks ini, penelitian ini menawarkan pendekatan hermeneutika sufi-ekofeminis sebagai alternatif pembacaan Al-Qur’an yang lebih holistik. Landasan teorinya mengintegrasikan kosmologi gender Sufi yang dikembangkan Sachiko Murata, yang menekankan keseimbangan kosmik antara maskulinitas dan feminitas, dengan kritik ekofeminisme Karen Warren yang menolak esensialisme dan menyoroti struktur patriarki, kapitalisme, serta kolonialisme sebagai akar penindasan terhadap alam dan perempuan. Metode penelitian menggunakan analisis kualitatif berbasis studi pustaka, dengan sumber utama berupa ayat-ayat Al-Qur’an, tafsir isyari klasik, serta karya-karya ekofeminisme kontemporer. Hasil penelitian menunjukkan bahwa integrasi Murata dan Warren menghasilkan kerangka tafsir non-esensialis yang menolak hierarki, menegaskan manusia sebagai penjaga keseimbangan kosmik, dan menempatkan kepedulian ekologis sebagai bagian dari spiritualitas Islam. Kesimpulannya, pendekatan sufi-ekofeminis membuka ruang tafsir Qur’an yang lebih inklusif dan transformatif. Dampaknya, penelitian ini tidak hanya memperkaya wacana tafsir dan filsafat Islam, tetapi juga memberi kontribusi praktis bagi pendidikan, dakwah, dan kebijakan ekologis yang berkeadilan gender serta berorientasi pada keberlanjutan.